(untitled) (CIPEEX, 2024)
This work aimed to present a legal approach to the institution of vacations in relation to the type of irregular work, going through the analysis of its historical evolution, its conceptualization, legal nature and the principles applicable to it and, consequently, the rights arising from it. Vacation is a worker’s right granted after a certain period of work. Its purpose is to provide rest and leisure, contributing to a dignified and humanized life. This work discusses the main aspects of the legal institution of vacations in the Brazilian context, considering its origins and its updating following the 2017 labor reform. After 12 months of work in the same company, employees are entitled to 30 days of vacation per year. Following. This benefit can be divided into up to three different vacation periods, which must be agreed with the employer. According to Brazilian labor legislation, one of these vacation periods must last at least 14 calendar days, while the others must be at least five calendar days. This vacation is paid at a high rate equal to the normal salary, plus one-third of the salary. Holidays are for 30 consecutive days per year and during this period the salary is increased by one third. However, unexcused absences from work may reduce vacation time. But in this aspect, the law is very considerate towards the worker, as deductions begin when there are more than 5 unjustified absences in the last year. The maximum is 12 days of vacation lost due to absence from work for more than 32 days.